INTEGRATION OF MECHANICAL AND CULTURAL CONTROL TREATMENTS TO MANAGE INVASIVE SHRUB Chromolaena odorata AND OTHER WEEDS UNDER DROUGHT CONDITIONS IN PASTURE AREA - Rusdy, M.; Sjahril, R.; Riadi, M.; Budiman, B. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
A field experiment was conducted on Chromolaena odorata dominated pasture with the objectivesof evaluating efficacy of integrated of mechanical and cultural control on weed suppression anddetermining botanical composition of plant species after treatment started. The treatments were, T1slashing of Chromolaena every month, T2 digging up of Chromolanea, and exposed to dry (mulching),T3 digging up of Chromolaena followed by burning, T4 digging up of Chromolaena followed byburning and sowing with Centrosema pubescens and T5 digging up of Chromolaena followed byburning and planting with Brachiaria decumbens. Results of experiment showed that under droughtconditions, digging up Chromolaena was very effective in suppressing regrowth of Chromolaena but itwas not effective to other weeds. Among treatments, digging out of Chromolaena followed by burningand planting with Brachiaria decumbens was the most effective and slashing of Chromolaena everymonth was the least effective in suppressing weeds. Botanical composition was shifted with treatments.Stachytarpheta jamaicensis and Chromolaena were the dominant species in monthly slashedChromolaena plots, Stachytarpheta and Calopogonium muconoides were the dominant species inmulched plots while Mimosa pudica, Brachiaria and Centrosema were the dominant species in burntplots.